The Effects of Repeated Reading on Reading Fluency for Students With Reading Disabilities: A Meta-Analysis. (March 2017) - Lee, Jiyeon; Yoon, So Yoon
The purpose of this research was to systematically review the effects of repeated reading (RR) interventions on reading fluency to provide instructional strategies for students with reading disabilities (RD). Correct words per minute were coded as an outcome variable in a search that yielded 34 RR intervention studies from 1990 to 2014 for students with RD in K-12. The estimated overall Hedges' g of the 39 independent effect sizes indicated the positive effects of RR on gains in reading fluency for students with RD, especially at the elementary grade level. The current findings also suggested that a combination of RR and a listening passage preview would be the most effective method for students with RD.